Expansion of Sinotaia quadrata (Mollusca: Gastropoda: Architaenioglossa: Viviparidae) in two major rivers from Argentina - Gutiérrez Gregoric, Diego Eduardo; de Lucía, Micaela; Torres, Santiago Hernán; Copa, Jorge Luis Esteban; Sánchez, Noelia Carolina; Darrigran, Gustavo Alberto (My University, 2024)
Invasive non-native freshwater mollusks are a growing concern in South America, with 16 species already recorded in the region. Among them, Sinotaia quadrata has only been documented in Argentina, for the first time in the Punilla Valley, Córdoba (2009) and La Plata, Buenos Aires (since 2015). In this study, we report the presence of S. quadrata in two additional areas, the Río de la Plata River and a stream (unnamed) in the Paraná River basin, two of the most significant rivers in South America, located in the provinces of Buenos Aires and Entre Ríos, respectively. These new records confirm the invasive nature of this species, which has also been identified in Europe, the United States, and Africa in recent years. The findings of this study highlight the need for continued monitoring and management of invasive species in South America’s freshwater ecosystems.
Keywords: Conservation; Dispersion; Invasive species; Río de la Plata River; Paraná River